Immunohistochemical Expression of bcl 2 and Ki-67 in Thyroid Neoplasms - Goswami, Vijyendra Puri; Kaur, Swaran; Gathwal, Monika B; Hooda, Sunaina; Sheoran, Tanu Priya (Annals of Pathology and Laboratory Medicine, 2025)
Background: Thyroid cancer is the most common endocrine cancer today. Its inci- dence has increased all over the world in the last three decades. An accurate diagnosis of thyroid neoplasm is therefore crucial as it has a major impact on the treatment modality as well as the patient's prognosis. This study was being done to determine utility expression of bel 2 and Ki-67 in thyroid neoplasms. Methods: This cross sectional study was conducted in the Department of Pathology at Bhagat Phool Singh Government Medical College for Women, Khnapur Kalan, Sonipat, Haryana. A total of 55 specimens were subjected to IHC (bel 2 and Ki-67). Results: Out of 55 thyroid neoplasm cases, 27 were benign and 28 were malignant. All the neoplastic pathologies showed varying degree of bel 2 positive expression. Ki-67 was negative in all benign neoplasms. Varying degree of positive expression was seen in malignant neoplasms: 100% positivity in follicular thyroid carcinoma (04/04), followed by 50% cases of invasive encapsulated follicular variant of papillary thyroid carcinoma (03/06), followed by 33.33% cases of papillary thyroid carcinoma (05/15). The expression of bel 2 was found to have 50.00% sensitivity and 33.33% specificity in thyroid neoplasms with diagnostic accuracy of 49.09%. The expression of Ki-67 was found to have 98% sensitivity and 67.50% specificity in detecting malignant thyroid neoplasms with diagnostic accuracy of 76.36%. Conclusion: Ki-67 proved to be useful marker in differentiating malignant thyroid neoplasms from the benign one as the Ki-67 labelling index more in the malignant neoplasms, it was statistically significant. The other IHC marker studied in the present study was bel 2 which acted as marker of proliferation for thyroid tissue, can help in detecting the metastatic foci in other organs and to diagnose the cases of poorly differentiated thyroid carcinomas.